Effect of atorvastatin on lipid and cardiovascular events in patients on maintenance hemodialysis - Azim, Muhammed Arshad Ul; Rahman, Md Habibur; Salam, Abdus; Islam, Sayed Mahtabul; Waheed, Shahryar (BIRDEM Medical Journal, 2019)
Background: Cardiovascular disease is the major cause of death in chronic kidney disease patient as well as in patients on hemodialysis. Dyslipidaemia is highly prevalent in patients on maintenance haemodialysis which increases the risk for cardiovascular mortality. This study was designed to evaluate the lipid abnormalities, effect of atorvastatin on lipid profile and cardiovascular events in patients on maintenance hemodialysis. Methods: In this prospective clinical study, 55 end-stage renal disease (ESRD) patients undergoing maintenance hemodialysis participated voluntarily. The study population was divided randomly into group-A (atorvastatin was prescribed) and group-B (without atorvastatin). We compared the lipid status and cardiovascular events of both groups after 6 months. Results: The two groups of patients were well matched in respect to baseline characteristics, history of risk factors and dialysis duration and session. Mean age of study population was about 48 years. Low density lipoprotein (LDL) cholesterol was reduced by 18.79%, total cholesterol was reduced by 9.32% and triglyceride was reduced by 22% in group-A. In group-A, high density lipoprotein (HDL) cholesterol was increased by 6% and it was reduced by 6% in group-B. In this study, myocardial ischemia/infarction on electrocardiogram (ECG) was present 22% in group-A and 14% in group-B at randomization. After 6 months, ischemia/infarction was found 33% in group-A and 25% in group-B. Statistically the ECG findings showed no significant changes after 6 months. In this study, mean ejection fraction (EF %) was 54% in group-A and 51% in group-B at 0 month, after 6 months atorvastatin group failed to show any significant change. In this study, after 6 months of statin therapy there was slight increase of serum glutamic pyruvic transaminase (16.13%) but that was not significant. Conclusion: In this study atorvastatin improved the lipid abnormalities significantly but a significant reduction of cardiovascular events was not achieved. Birdem Med J 2020; 10(1): 34-39